DAMPAK PENYELENGGARAAN EVENT PARIWISATA DRAGON BOAT RACE DI KOTA TANJUNGPINANG - Rahayu, Ida (Jurnal Master Pariwisata (JUMPA), 2018)
The development of the Dragon Boat Race tourism event was adopted from the religious activities of the Chinese commu- nity in Tanjungpinang City will indirectly generate an impact as a consequence of its implementation. This study aims to de- termine the impacts generated by the Dragon Boat Race Event on environmental, socio-cultural and economic aspects. This research used qualitative method and data obtained through observations, interviews and literature study. Data analysis used is descriptive-qualitative with qualitative descriptive exposure. Informants in this study are 16 people whom were selected purposively. The results show that the impact of the event of Dragon Boat Race tourism in general has some posi- tive snd negative impacts. Positive impacts on the environ- ment is the opening of the land; on the social and cultural is the creation of social interaction and international relations; and positive impact on the economy is increasing income and providing employment opportunities. Negative impacts on the environment is traffic density and noise created around the Carang River area; on the social and cultural is social dis- parities between local communities, government and private parties. This gap occurs because of differences in social status between them; on the economy is uneven benefits and profits for local communities since not many people aware of the im- portance of their participation in Dragon Boat Race.